The use of somatic cell counts to identify cows with subclinical mastitis at calving - J. M. Sargeant; B. J. Pulkrabek; Michael V. Scheffel; A. F. Park (Kansas Agricultural Experiment Station Research Reports, 1999)
The dynamics of somatic cell counts during the first 10 days in milk were compared among udder quarters of cows with intra-mammary infection at the time of calving and those with no infection present. The study group consisted of 81 cows calving at the Kansas State University dairy research herd between July of 1998 and February of 1999. Cows with an intramammary infection had greater, average, somatic cell counts at calving, and this difference continued throughout the 10-day period. Using a breakpoint of 1,000,000 somatic cells/ml at calving to select animals for culture would have correctly selected 81% of the quarters that were actually infected with major mastitis pathogens.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Somatic cell count; Intramammary infection; Calving